The effect of using the total physical response (TPR) method to teach phrasal verb for young learners’ in English teaching - Cindy Canora; Setiyadi, Ag. Bambang; Riyantika, Fajar (English Language Education Study Program, 2024)
Abstract. This research aimed to find out whether there was an statistically significant increase in students' after the implementation of Total Physical Response (TPR) Method. The research was quantitative research using one group pretest and posttest design. The samples of this research were thirty students in class V-Multazam at SDIT Insan Kamil Bandar Jaya in the academic year 2023/2024. The data were collected using pretest and posttest of vocabulary test. In order to analyze the result, Paired Sample T-Test was used to test the hypothesis. it was proved by the increase of students' mean score in the pretest was 34.13 and the students' mean score in the posttest was 74.51. It showed that the gain of students' improvement was 40.37. The result showed that there was a statistically significant increase of students' vocabulary with significant level (0.00<0.05) and the t-value (17.330) were higher than t-table (2.048). This suggest that teaching vocabulary using Total Physical Response (TPR) method facilitates students to improve their phrasal verbs. Keywords: Young Learners, Phrasal Verbs, Total Physical Response.